2013
DOI: 10.1007/s10597-013-9673-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Primary Care Activities in ACT Teams

Abstract: Background People with serious mental illness often receive inadequate primary and preventive care services. Federal healthcare reform endorses team-based care that provides high quality primary and preventive care to at risk populations. Assertive Community Treatment (ACT) teams offer a proven, standardized treatment approach effective in improving mental health outcomes for the seriously mentally ill. Much is known about the effectiveness of ACT teams in improving mental health outcomes, but the degree to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
2
14
0
1
Order By: Relevance
“…68 One advisory group field expert described research undertaken within their trust that identified a number of staff-related barriers to improving physical health for people with SMI, including knowledge (e.g. a lack of knowledge of recommendations); skills (e.g.…”
Section: Training and Education For Mental Health Practitionersmentioning
confidence: 99%
“…68 One advisory group field expert described research undertaken within their trust that identified a number of staff-related barriers to improving physical health for people with SMI, including knowledge (e.g. a lack of knowledge of recommendations); skills (e.g.…”
Section: Training and Education For Mental Health Practitionersmentioning
confidence: 99%
“…Recovery focused care that encourages the person to lead a productive life with meaning, hope and purpose beyond the effects of mental illness (Slade 2010) is also firmly embedded in these policy statements (Australian Health Ministers 2009;Department of Health 2011;Mental Health Commission of Canada 2012). However, as a group, people with a mental illness still face many obstacles in their recovery journey that include the high rate of physical health co-morbidities and mortality (Park et al 2011;Shuel et al 2010;Stanley & Laugharne 2012;Tosh et al 2011;Tranter et al 2012;Vanderlip et al 2014;Viron et al 2014;Weiser et al 2009;). They are likely to have at least one chronic medical condition and to develop that illness at a younger age than the general population (Bezyak et al 2011;El-Mallakh et al 2010;Galon & Graor 2012;Viron & Stern 2010;Wiley-Exley et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ACT teams are more specifically inspired by the PACT (Program of Assertive Community Treatment) model, which has demonstrated its effectiveness on the international scene (United States, Canada, United Kingdom, etc.) (Vanderlip et al, 2014). Essentially, the PACT model promotes intervention in the community through the support of a multidisciplinary team (consisting of 10 members belonging to different professions) that takes a long-term, proactive approach with users, with a special focus on basic needs such as housing, food, medical care, and the like (Thomson et al, 2002).…”
Section: Case Studymentioning
confidence: 99%